Beyond the Clinic: Parental Experiences and Developmental Outcomes of Home-Based ABA Intervention for Autism in Nepal - Wu, Sinong (Academia Journal of Humanities & Social Sciences, 2026)
The purpose of this study was to explore the personal experiences of families with autism in Pokhara Metropolitan City, Nepal, especially dealing with their challenges and child developmental outcomes during the implementation of a home-based Applied Behavior Analysis (ABA) intervention. As a developing country, Nepal has significant gaps in the localized application and research of ABA. For this reason, this study used an interpretive sequential mixed methods approach to integrate quantitative and qualitative data by administering questionnaires to 30 parents of children with autism in a phased manner and conducting in-depth semi-structured interviews with two of these typical families. The results of the study showed that although parents generally recognized the role of ABA in improving family organization and daily norms, the overall satisfaction with the intervention was extremely low, with 76.67% of the families expressing “dissatisfaction”. Children showed some progress in eye contact and behavior management, but very limited development in language and communication. Families generally faced multiple pressures: heavy financial burdens, overburdened mothers as primary interveners, lack of training resources, and weak social support systems. Qualitative interviews further revealed that insufficient financial subsidies, a disconnection between training and practice, and a lack of ongoing professional guidance are major barriers for families in implementing ABA. The findings of this study suggest that a direct transplantation of the internationally utilized ABA intervention model in Nepal would face significant adaptation deficits. The future support systems should be more focused on developing adaptive programs that fit into Nepal’s cultural, economic, and family structures. As the first exploratory study of family-based ABA interventions in the region, this study provides an important empirical basis and direction for subsequent research and practice.